3x-3(5-2x)=3

Simple and best practice solution for 3x-3(5-2x)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-3(5-2x)=3 equation:


Simplifying
3x + -3(5 + -2x) = 3
3x + (5 * -3 + -2x * -3) = 3
3x + (-15 + 6x) = 3

Reorder the terms:
-15 + 3x + 6x = 3

Combine like terms: 3x + 6x = 9x
-15 + 9x = 3

Solving
-15 + 9x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + 15 + 9x = 3 + 15

Combine like terms: -15 + 15 = 0
0 + 9x = 3 + 15
9x = 3 + 15

Combine like terms: 3 + 15 = 18
9x = 18

Divide each side by '9'.
x = 2

Simplifying
x = 2

See similar equations:

| 8a^3+27b^3+64c^3=72abc | | 9(2X-1)=3(3x+3) | | 1p+2=-1 | | 3(2x+3)=2(3x+1) | | 2a^2-5a-4=0 | | 3u^2+12u+6=0 | | x(x-4)(x+11)=0 | | 4d*-3d= | | (28-4i)-(10-30)=0 | | 3+8x=14-3x | | 1-4(100+36s)=15-4s | | y^2-4y=8 | | 8x+8-ax-a=0 | | 3(x-3)=2(x-2)-(5-3x) | | 0.50(8n-2)=16-30n | | 2x^2+10x-80=0 | | x(2x+3)(x-4)=6 | | x(2x+5)(x-4)=6 | | 9m+5-4m=-20 | | 13x-30=7x-14 | | -6(x-3)=-3(x+9) | | (x-p)(x^2+11x+15)=(x^2-9)(2x+q) | | 2x^2-3-15=0 | | k+84738398=98393398 | | 8+9t=21t-17 | | X^2+.52x=-25 | | 3(b+4b)=40-15+20 | | -4(w-3)-6w=-2(w+6) | | 0=0.4t^2-7.7t+0.5 | | 0.2+10000= | | 3+9*2= | | 2(x-6)+3(2-3x)=5(2x-1)+4x-1 |

Equations solver categories